Education in Indonesia (Merdeka Curriculum) and Japan Curriculum : Whatâ€™s the Difference? - Prakoso, Albrian Fiky; Andriansyah, Eka Hendi; Rafsanjani, Mohamad Arief; Nurlaili, Eka Indah; Arif, Amirul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
The purpose of this study is analyze of the differences in education between Indonesia, which has begun to develop an independent curriculum, and education in Japan. This study used the systematic literature review method. The population consists of 99 articles that discuss education in Indonesia and Japan, and were published between 2010 and 2022. From 99 articles, 29 articles were sampled. This study used documentation instruments in the form of articles published with criteria for selecting these 29 articles as samples, which were articles published in nationally accredited journals, indexed proceedings, and Scopus-indexed international journals and then analyzed using thematic analysis. The results obtained are that the Â significant fundamental differences in education in Japan and Indonesia lie in international education, character education, ethics and discipline and fields of study. The implication of this research is that in the development of a new curriculum, elements of culture and values are still prioritized as the characteristics and profile characteristics of graduates.